1996
DOI: 10.1097/00006534-199603000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Severe Contractures of the Proximal Interphalangeal Joint in Dupuytrenʼs Disease: Combined Fasciectomy with Capsuloligamentous Release Versus Fasciectomy Alone

Abstract: Severe proximal interphalangeal joint contracture in Dupuytren's disease presents a frustrating problem for hand surgeon. Some surgeons argue for fasciectomy alone, avoiding violation of the proximal interphalangeal joint, which may prolong morbidity and result in permanent limitation of flexion; this loss of flexion can be more disabling than a mild flexion contracture. Others favor capsulotomy in addition to fasciectomy, especially for severe contractures, to obtain additional release, arguing that one canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 13 publications
2
16
0
1
Order By: Relevance
“…Some researchers 11 have suggested that joint release is not useful, but in that study the patients were not randomized and may have been subject to selection bias. More recently, when studying patients with PIPJ flexion deformity of at least 60°, patients who achieved full correction at the time of surgery had an almost identical final residual deformity (15°) at 6 months when compared with those requiring joint release (16°) to improve residual preoperative deformity after fasciectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers 11 have suggested that joint release is not useful, but in that study the patients were not randomized and may have been subject to selection bias. More recently, when studying patients with PIPJ flexion deformity of at least 60°, patients who achieved full correction at the time of surgery had an almost identical final residual deformity (15°) at 6 months when compared with those requiring joint release (16°) to improve residual preoperative deformity after fasciectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This study failed to report proximal interphalangeal joint extension after excision of the diseased fascia and after capsuloligamentous release. Weinzweig et al (1996) performed a retrospective review of flexion contractures (601 or greater) involving 42 proximal interphalangeal joints in 28 patients with Dupuytren's disease. Twenty-seven joints in 18 patients underwent fasciectomy alone, and 15 joints in 10 similar patients underwent capsulotomy in addition to fasciectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is as secondary contracture of the joint capsule and ligaments can prevent complete correction of the deformity. Some surgeons feel that at least partial division of the capsuloligamentous structures should be done to correct the joint contracture (Rives et al, 1992;Watson et al, 1979;Weinzweig et al, 1996), while others advice against capsulotomy, arguing that any benefit will be short-lived, and that the surgical assault will cause further scarring and contracture (Hueston, 1991;McFarlane, 1974). This prospective study assesses whether patients with severe proximal interphalangeal joint contractures due to Dupuytren's disease which does not correct with fasciectomy alone benefit from an additional capsuloligamentous release.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) We have generally performed regional fasciectomy because needle fasciotomy alone is associated with a higher recurrence rate, together with primary wound closure (or skin grafting) because it causes less soft tissue contracture, gentle passive manipulation of the PIP joint to avoid complications, and immobilization of the PIP joint with Kirschner wire to restore the extensor tone. [1][2][3][4] Despite these measures, we do not always achieve satisfactory maximum active extension and painless postoperative PIP joint motion, especially when the little finger is severely affected.…”
Section: Discussionmentioning
confidence: 88%